Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Quispe Hure, Alvaro German (2019)
With over USD 290 million in 2015 revenues and over 5,000 hectares of crop, Camposol is one of the leads agroindustry companies in Peru and one of the major players all over the globe. Its focus is on the growth of blueberry and avocado categories and its main target markets are USA, Europe and, currently, it is incrementing its commercial effort in China. Camposol activities are present all over the value chain and its main characteristic is that it is flexible enough to commercialize its products frozen, preserved or fresh. One of the company’s strategic goals is to become the biggest blueberry producer in the world. In that sense, this case presents a depth analysis of the current situation of Camposol, the strategies they are following considering the opportunities and challenges ahead and recommendations on what they could implement to be the biggest blueberry producer, to achieve other long-term objectives and improve its profitability.